Marienborgmødet den 21. august 1975. 1970’ernes økonomiske debat, mimsen og de økonomiske vismænd - Kærgård, Niels; Skou (†), Niels Holger (Historisk Tidsskrift, 2024)
The Marienborg Meeting 21 August 1975: The Economic Debate of the 1970s, VAT reduction and the Economic Magi In 1973–1974, the impact of the first oil crisis was felt worldwide. In Denmark, unemployment soared from less than 50,000 unemployed in the years before 1974 to around 250,000 in the early 1980s. This gave rise to heated debates on the available economic-political instruments. In this connection, the government arranged a meeting on 21 August 1975 at Marienborg and invited all 15 professors of economics at Danish universities to attend. The meeting resulted in a temporary reduction of VAT, with effect from 29 September 1975. This meeting and the temporary VAT reduction are of interest for several reasons: First, it provides insight into the interaction between economic experts and politicians, and into the mindset of Danish economists in the mid-1970s. They believed firmly in Keynesian fiscal policy and expected the economic crises soon to subside. Experience proved them wrong. Second, it shows that the unsuccessful economic policy in the 1970s was not due to incompetent politicians, but mainly to wrong advice from the country’s best economic experts. Third, the Marienborg meeting became a milestone in the history of the Danish Economic Council (the so called Economic Wisemen) because the occasion for the meeting was the refusal of the chairmen of the Danish Economic Council to act as the government’s confidential economic advisors. This confirmed the status of the Council as an independent institution and endowed it with great authority in public opinion.